Relation between maximum oxygen uptake and anaerobic thershold and the rowing ergometer results for senior rowers - Jurisic, D.; Donadic, Z.; Lozovina, M. (Acta Kinesiologica, 2014)
In accordance with the worldwide achievements in the area of sports physiology, Croatian rowing has established its own protocol for controlling the competing form of rowers. The developed progressive discontinuing workload test was carried out on a rowing ergometer, and it was developed for the purpose of determining the maximum oxygen uptake and lactate anaerobic threshold, i.e. the "lactate curve". It is the finest and the most precise laboratory test in use. It is used to control the training process with the purpose of programming, i.e. reprogramming the rowers' training. The experimental section of the paper describes a test carried out on a sample of 30 rowers of the national and international calibre which demonstrated a statisticaly significant correlation between the rowing velocity at anaerobic threshold with maximum oxygen uptake (r = -0,6139). A significant individual impact of maximum oxygen uptake and rowing velocity at anaerobic threshold on the rowing simulator result at 2000m was also identified. There is a stronger correlation between the rowing velocity at anaerobic threshold and the rowing simulator result at 2000m (r = 0,72) than between the VO2max and the rowing simulator result at 2000m (r = -0,55). Taking the production of lactic acid as an indicator of the rower`s competing form, it was expected, from the statistical point of wives, that it will be a highly significant predictor of the maximal test result. A strong and statistically significant co-reactive correlation between maximum oxygen uptake and lactate anaerobic threshold, as well as their strong correlation with the rowing simulator test result at 2000m, confirms the assumption that the aerobic metabolism predominantly determins the success in a 2000m rowing race (on a simulator).